Predictive value of umbilical cord blood albumin levels as an indicator of neonatal jaundice in healthy term newborns - Bhat, Prerna; Agarkhedkar, S.R.; Salunke, Shradha (Indian Journal of Child Health, 2020)
Background: Neonatal hyperbilirubinemia (NH) is the most common cause of readmission during the early neonatal period. There is a need to find the methods of screening babies at higher risk of developing jaundice before discharge. Objectives: The objectives of this study were to find out the predictive value of cord serum albumin (CSA) levels as an indicator of neonatal jaundice. Materials and Methods: A cross-sectional study conducted at a tertiary hospital of Maharashtra, from October 2017 to September 2019 on 410 term newborns. CSA was collected at birth and correlated with serum bilirubin levels collected at 48 h of life. Statistical analysis was performed and the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) with a 95% confidence interval obtained. Results: Of 410 cases, 266 (64.8%) developed clinical jaundice, of which 148 (93.6%) had albumin levels 3.3 g/dl. At CSA level